Media in the Cultural Dissemination: A Study of Cultural Filming on YouTube - Irsyadi, Achmad Naufal; Madamidola, Oladele (Fakultas Bahasa dan Seni, 2023)
Media played a role in the dissemination of all kinds of information quickly and thoroughly, especially disseminating cultural information in order to maintain the value of culture. We studied and reviewed the potential of YouTube as a visual medium in disseminating the forms and values ​​of culture. We used Denis McQuail's theory of mass communication in the field of new media theory. In our assumption, YouTube has visual-ideological compatibility in presenting a number of cultural portraits whose elements and values ​​can be listened to, identified, and internalized by the audience as something useful and valuable. Thus, there were at least two things that could be obtained from a culture broadcast on new media, namely (a) elements and values ​​of a culture could be spread to the public and serve as useful values ​​for life, and (b) elements and values of a culture could be maintained.